THE USE OF VIDEO-BASED MULTIMEDIA LEARNING MEDIA IN FIKIH SUBJECT MATERIALS OF HAJJ WORSHIP - Mutawakkil, M. Hajir (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2023)
This research aims to describe the implementation of video-based multimedia in class V fiqh learning material on the Hajj pilgrimage at MI Tarbiyatul and its impact on teachers and students. This research starts from a case in learning; some teachers still need to use suitable media, so students do not understand and are less enthusiastic about learning. This research uses a qualitative approach with a case study type. Data collection techniques using observation, interviews, and documentation. The data analysis technique consists of three activities: data reduction, data display (data presentation), and conclusion drawing/verification (conclusion). The research results show that the use of video media in learning Islamic jurisprudence material on Islamic worship at MI Tarbiyatul Islam class V is excellent and efficient. This cannot be separated from the teacher's readiness in planning and applying the media and the availability of infrastructure in the educational institution. The impact of using video media for teachers includes making it easier to convey material, saving energy in explaining, and encouraging teachers to develop learning media. Meanwhile, the impact on students includes students who can focus more on learning, foster interest in the subject matter, are motivated to learn, and make it easier for students to understand the material